Hyposalivation but not Sjögren’s syndrome associated with microbial dysbiosis in women - Saúco, Carlos; Rus, Maria J.; Nieto, María R.; Barros, Carolina; Cantiga-Silva, Cristiane; Lendines-Cordero, Débora; Calderer-Ortiz, Marta; Zurita-García, Miriam; Arias-Herrera, Santiago; Monsalve-Guil, Loreto; Segura-Egea, Juan José; Simon-Soro, Aurea (Frontiers in Microbiology, 2023)
Background: Saliva modulates the environment of the oral biofilm through pH buffer, microbial attachment to host surfaces, and nutritional source. The ecology of stress occurs when a physical factor adversely impacts an ecosystem or its biotic components. Therefore, reduced salivary flow can affect oral-host balance. The leading causes of hyposalivation include disease-associated Sjögren's syndrome (SS) and menopausal women as aging-associated. However, little is known about the oral microbiome integrated with sex hormones in hyposalivation. This study aimed to characterize the hyposalivation microbiome caused by aging or disease affecting the salivary glands in women.Methods: We included 50 women older than 40 years of age in any menopausal phase. We collected stimulated saliva from 25 women diagnosed with SS (SS) and 25 without SS (non-SS). The bacterial profile of the patients was obtained by 16S rRNA sequencing. Bioinformatics analysis used machine learning to analyze the cohort's signs, symptoms, and bacterial profile. Salivary estradiol as a sex hormone variation level was determined.Results: We obtained that 79% of the SS group, and 52% of the non-SS group had hyposalivation. We found a negatively correlated Prevotella-age and Rothia-estradiol in the SS group. Highlight, we found that the cause of the hyposalivation in the study did not explain differences in microbial diversity comparing non-SS and SS groups. Therefore, microbial communities found in hyposalivation but not related to systemic conditions suggest that changes in the oral environment might underpin hostmicrobial balance.Conclusions: The salivary microbiome was similar in women with and without SS. However, hyposalivation showed two distinctive clusters associated with the bacterial population profiles. Our study suggests that local ecological disturbances could drive the change in the microbiome.